Implementasi Pemeriksaan Lumbosacral pada Kasus Scoliosis di Instalasi Radiologi BLUD Rumah Sakit Umum Daerah Cut Nyak Dhien Meulaboh - Pocut Zairiana Finzia; Dewi Febriyanti; Shoriyah Sartika (INSOLOGI: Jurnal Sains dan Teknologi, 2023)
The aim of this study was to find out how the implementation of the lumbosacral examination in cases of Scoliosis and how to describe the quality of radiographic images on lumbosacral examination using Anterior Posterior (AP) Projection, Lateral Projection, and Anterior Posterior Projection bending left and right in terms of detail and sharpness. This study was conducted with three exposures to one patient who was diagnosed with lumbosacral scoliosis using the same distance but with different projections. The results of this study are in the form of lumbosacral radiographs and distribution frequency tables of ten radiographer respondents. The results showed that the lumbosacral examination in cases of scoliosis at the Radiology Installation BLUD, Cut Nyak Dhien Hospital, Meulaboh, West Aceh can use three different projections, namely anterior posterior projection, lateral projection and anterior posterior bending left right projection. The quality of the lumbosacral radiograph images produced in cases of scoliosis is clear and good in detail and has a sharpness level from the distance, patient movement, and the use of the viewing box.